Highly pathogenic bovine viral diarrhea virus BJ-11 unveils genetic evolution related to virulence in calves - Zhang, Yuanyuan; Cheng, Jing; Guo, Yu; Hu, Yibin; Zhao, Zhuo; Liu, Wenxiao; Zhou, Linyi; Wu, Peize; Cheng, Chunjie; Yang, Chun; Yang, Jing; Du, Enqi; et al. (Frontiers in Microbiology, 2025)
Bovine viral diarrhea virus (BVDV) is the causative agent of bovine viral diarrhea, which causes significant economic loss to the global livestock industry. Despite the widespread use of inactivated BVDV vaccines, highly pathogenic strains continue to emerge. In China, regional variations in BVDV subtypes, morbidities, and symptoms, however, only the BVDV 1a subtype vaccine is currently approved. Therefore, this study is to gain insight into the biological characteristics and genetic variation of BVDV strains prevalent in Beijing. Meanwhile, this will provide a theoretical foundation and technical support for the prevention and control of BVDV, as well as raise awareness of the potential for virulence enhancement caused by the unregulated use of BVDV vaccines. In this study, A BVDV strain, BJ-11, was isolated from calves that died of diarrhea and vaccinated of BVDV. To evaluate its virulence, newborn calves were experimentally infected with the BJ-11. Clinical signs included fever, diarrhea, bloody stools, anorexia, and death in some cases. A marked reduction in leukocyte and lymphocyte counts were observed, accompanied by an increase in neutrophil counts. Histopathological changes manifested as severe lung lesions. Phylogenetic analysis indicated that BJ-11 belongs to the BVDV 1b subtype, genetically closest to the JL-1 strain. Analysis of the E2 glycosylation site disappeared (298SYT) in one of the four common glycosylation sites in the BVDV-1, which has been reported to affect the ability of the virus to infect and an additional glycosylation site (122NGS). These results indicate that BJ-11 is a highly pathogenic strain evolved from a low-virulence ancestor and should be served as a challenge strain. Simultaneously, these results contribute to a broader understanding of BVDV and whether imperfect vaccination strategies lead to reversal of immunosuppressive virulence.